2017
DOI: 10.5194/gmd-10-4443-2017
|View full text |Cite
|
Sign up to set email alerts
|

A data-driven approach to identify controls on global fire activity from satellite and climate observations (SOFIA V1)

Abstract: Abstract. Vegetation fires affect human infrastructures, ecosystems, global vegetation distribution, and atmospheric composition. However, the climatic, environmental, and socioeconomic factors that control global fire activity in vegetation are only poorly understood, and in various complexities and formulations are represented in global process-oriented vegetation-fire models. Data-driven model approaches such as machine learning algorithms have successfully been used to identify and better understand contro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
107
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 61 publications
(115 citation statements)
references
References 120 publications
3
107
0
3
Order By: Relevance
“…We simulated burned area using an empirical fire model based on the SOFIA (Satellite Observations for FIre Activity) approach, which estimates monthly burned area from observed time series of land cover, vegetation, climate variables and human population density (Forkel et al 2017).…”
Section: Burned Area Datamentioning
confidence: 99%
See 1 more Smart Citation
“…We simulated burned area using an empirical fire model based on the SOFIA (Satellite Observations for FIre Activity) approach, which estimates monthly burned area from observed time series of land cover, vegetation, climate variables and human population density (Forkel et al 2017).…”
Section: Burned Area Datamentioning
confidence: 99%
“…Indeed, analyses of the FireMIP simulations suggest that, while they represent the climate controls on burned area reasonably well, they underestimate the sensitivity to previousseason plant productivity and have over-simplistic representations of the influence of human activities on burned area (Forkel et al 2019). Empirical fire models (Moritz et al 2012, Bistinas et al 2014, Forkel et al 2017 provide an alternative and arguably better approach to reproduce observed fire dynamics and to quantify the relative importance of climate, vegetation and human factors on temporal changes in burned area.…”
Section: Introductionmentioning
confidence: 99%
“…Biomass burning is one of the key processes affecting vegetation productivity, land cover, soil erosion, hydrological cycles and atmospheric emissions Forkel et al, 2017;Gaveau et al, 2014;van der Werf et al, 2017). It has social implications as well, impacting people's lives and properties (Roos et al, 2016), particularly in developed countries where urban areas are intermixed with forests (Bowman et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Fire is affected by climate, as burnings are associated with high to extreme weather conditions (particularly droughts and heatwaves) (Forkel et al, 2017). However, fire affects climate too, due to its impacts on carbon budgets and greenhouse gas emissions (van der Werf et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation